DECISION SUPPORT SYSTEM TO DETERMINE BLACK PEPPER GRAIN QUALITY IN PEKON DETERMINATION USING SIMPLE ADDITIVE WEIGHTED - Krisna Dwi Saputra (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2021)
Pepper is one commodity exports from Indonesia. Black pepper seed quality for export include some criteria predetermined. However, in determining the quality of black pepper seeds is often constrained this is still a lack of public knowledge about the quality of black mustard seeds. Problem that makes researchers want to create a system that can help the decision support pepper farmers in determining the quality of black pepper seeds. In making the Decision Support System was built taking several criteria such as water content, seed weight, levels of foreign body, and the fruit skin color. The system was built using Simple Additive Weighted method. The existence of Decision Support System to help farmers in determining the quality of the seeds of black pepper quickly and accurately by incorporating the criteria found in the field into the system, and the calculation of SAW result that varieties Petaling 2 is a quality black pepper highest with a value of 1